Sensitivity, Specificity, and Accuracy of Kramer Examination of Neonatal Jaundice: Comparison with Total Bilirubin Serum. (30th November 2017) - Aprillia, Zesi; Gayatri, Dewi; Waluyanti, Fajar Tri
ABSTRACT: Neonatal jaundice often occurs in the first week after birth. Early detection of neonatal jaundice can prevent kernicterus as a complication of high levels of bilirubin in neonates. Visual assessment is one of the examinations introduced by Kramer to assess the presence of neonatal jaundice. The purpose of this study was to determine the sensitivity, specificity, and accuracy of Kramer's visual assessment in the examination of neonatal jaundice. This study used cross-sectional design to examine 102 infants, with the sample selected by the convenience sampling method. A 2 × 2 table diagnostic test was employed in this study to analyze the data. The results of this study showed that visual assessment of neonatal jaundice obtained a sensitivity value of 76.92%, a specificity value of 89.47%, and an accuracy value of 86.27%. This research can contribute to the development of other non-invasive methods for assessing neonatal jaundice, and thereby contribute to a decrease in neonatal morbidity.